(3fSHI GQJaGY CYXe GdLHGd Ydi bWQ Edi bWQ GdCQVs - (3GdMGQKj GdYGedj GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s
(3ChdgG (B:s
(3fMeOc jG ef Lgd GdCQV egGOG (B... (3EP hbY GdfXQ GdbGUQ (B.. (3Ydi GdHMK GdeTJgQ GTJgGQ GdTeS aj hSW GdfgGQ CYfj eHMK fSHI GQJaGY CYXe GdLHGd Ydi bWQ Edi bWQ GdCQV ef TQM GdLZejfj MTQg Gddg jhe GdbjGeI eY (B..s
(3BNQgG (B:s
... (3dCf fSHI GdcQI Ydi GdcQI cfSHI GdbWQ Ydi GdbWQ eKdKI HGdJecQjQ hcPc fSHI GdecYH Ydi GdecYH cfSHI GdVdY Ydi GdVdY eKdKI HGdJcQjQ dCf ecYH GdhGMO hGMO hecYH Cda hKeGfjI gcPG (B...s
(3JHUQI GdYfhGf (B:s
(3QO Ydi TQM GdLZejfjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\102s
(3GdPQjYI (B24/721s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG hGdHdOGfs